Competence and competency in the EQF and in European VET systems - Brockmann, Michaela [Verfasser]; Clarke, Linda [Verfasser]; Winch, Christopher [Verfasser] (My University, 2009)
"Though the notion of competence is common terminology in European VET policy at national and supra-national level, understandings vary widely, both across countries and within. The particular conceptions of competence adopted in the EQF are themselves problematic and the framework allows for a variety of interpretations. The purpose of this paper is to clarify those applied in the EQF and the vocational education and qualifications systems of particular European countries and to contribute to the development of a transnational understanding of the term, one which is compatible with a rapidly changing labour market. Drawing on evidence from work funded by the Nuffield Foundation entitled 'Cross-national Equivalence of Vocational Skills and Qualifications', the paper explores the various conceptions of competence in the EQF and the national systems: in particular in the sectors of construction, ICT and health of England, Germany, France and The Netherlands." (Autorenreferat, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.2.1 Westeuropa; Kompetenz; Begriff; Europäischer Qualifikationsrahmen; Nationaler Qualifikationsrahmen; Beziehung Bildungssystem Beschäftigungssystem; Internationaler Vergleich; Bundesrepublik Deutschland; England; Frankreich; Niederlande